Horizontal and Vertical Analysis of Privacy and Cyber-Security Markets - Nicola Jentzsch (Waterford Institute of Technology (WIT), 2015)
Deliverable 4.2 (“Horizontal and Vertical Analysis of Privacy and Cyber-Security Markets”) provides an in-depth discussion of economic incentives, stakeholder engagement and market opportunities in privacy and cyber-security. This report first introduces the reader to the horizontal market analysis, which covers firms active at the same stage of the production chain in the privacy and cyber-security industry and present key market segmentations.The report also presents the vertical analysis of players at different stages of the production chain in the PACS industry. These relations are covered as security in the supply chain is of utmost importance: only secure inputs ensure a secure product as final output. The report also covers engagement and assessment of stakeholders in the privacy and security chain and their relation to PACS in the ICT sector. The report gives several case studies on vertical relations and includes an empirical analysis of incentive schemes. The proposed innovation value chain connects inputs and outputs in the production of PACS goods and services and their relation to economic incentives.Finally, a preliminary scheme on mapping privacy and personal data product and service markets is proposed. Firms active in these markets can be categorized according to their generic value chain, where some use the identification of the user as key input and others do not. The report provides economic incentive templates that enable market players and regulators to potentially better map the markets.The following scheme outlines in brief the relation of the two deliverables D4.1 and D4.2 to the developed Privacy and Cyber-Security Market Scheme. It enables the reader to see what is covered in the different deliverables and to what deliverable he/she needs to turn in order to find the information of interest.
info:eu-repo/grantAgreement/EC/FP7/609892
Keywords: 330; Sicherheitstechnik; Datensicherheit; Marktanalyse